PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS KETERAMPILAN LITERASI - S.Sirate, Sitti Fatimah; Ramadhana, Risky (Universitas Islam Negeri Alauddin Makassar, 2017)
This study aims at developing a literacy-based instructional module on social arithmetic that can help the learning activities of grade VII students of Junior high school 1 of Gantarangkeke Bantaeng regency in order that they are more independent in reviewing, interpreting, interpreting, reasoning and communicating effectively and solving math problems in various contexts in everyday life. The type of this research is Research Development (Research and Development) by using modification of 4-D model combined with Romiszowski model. The model 4-D is taken only at the design level, especially on the aspect of choosing the teaching material development format, while the Romiszowski model includes three stages: (1) analysis, (2) synthesis and (3) evaluation, and all three stages are at the structural level of the second part of the Romiszowski model schema which emphasizes the development of printed materials in this case the product in the form of a learning module that meets the valid, practical and effective criteria. The results showed that the literacy-based math learning module meets the valid and practical criteria with a score of 3.73 including the highly valid category, and the 3.37 score belongs to the category of good in terms of practicality. This learning module also meets the effective criteria with the percentage completeness 79,19% which is in good category. Thus, the developed literacy-based math learning module has fulfilled the valid, practical and effective criteria. Keywords: model devepoment, media and technology, instruction